Influencia de la cobertura vegetal ribereña sobre los macroinvertebrados acuáticos y la calidad hídrica en ríos del bosque protector Murocomba, cantón Valencia, Ecuador - Yong Benítez, Ronny Emilio (2015)
This research was conducted between the months of June, July, August and October, in three streams with different mulches (The Congo, La Victoria, La Damita) Murocomba Protector Forest, part of the canton Valencia province of Los Rios . To evaluate the influence of three types of riparian vegetation cover on communities of aquatic macroinvertebrates and water quality. Collection of aquatic macroinvertebrates was developed every 45 days for four months using a network type "D" Net; insects were placed in containers with 70% alcohol, for which entomological forceps were used. The samples of macroinvertebrates moved to the laboratory for analysis; identification is performed using a stereoscope and taxonomic keys. The physicochemical parameters: total dissolved oxygen, temperature, conductivity, dissolved solids, potential hydrogen were measured in situ. Quality Index Bosque de Ribera (QBR) was used for the evaluation of plant cover. The orders were more abundant Caddis (30.4%), Coleóptera (26.25%), Ephemeróptera (13.35%), Díptera (12.59%), and Plecóptera (10.12%). In the ravine "Congo" dissolved oxygen was recorded within permissible limits while Quebrada La Victoria and Damita found outside the permissible limits. Besides electricity, total dissolved solids conductivity, temperature, hydrogen potential presented values within permissible limits set by the (WHO, 1993, EPA, and Ministerial Agreement 028) standards. Broken Congo introduced a degree of plant coverage "Strong alteration, poor quality" Victoria determined a "Forest undisturbed Rivera" La Damita fluctuated in a "Home Alteration Important". ….